2013
DOI: 10.1001/jamaophthalmol.2013.2308
|View full text |Cite
|
Sign up to set email alerts
|

Cultivated Limbal Epithelial Transplantation in Children With Ocular Surface Burns

Abstract: Importance: Although several reports are available on the use of conventional and cultured limbal epithelium using various substrates in the treatment of limbal stem cell deficiency (LSCD), the patient populations studied have been largely adults. Thus, to our knowledge, the outcomes of this procedure exclusively in a pediatric population have not been reported previously. Objective: To report the outcomes of autologous ex vivo cultivated limbal epithelial transplantation (CLET) in pediatric patients with LSCD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
76
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 23 publications
(31 reference statements)
1
76
1
1
Order By: Relevance
“…As for the condition of donor eyes, which was mentioned in 4 studies, 25,28,30,32 no complications were reported. Following CLET, in 7 studies 25,28,31,34,37,38,41 it was reported that 18 eyes were suffering from microbial keratitis, but through fortified topical antibiotics or emergency keratoplasty 11 eyes were fully cured.…”
Section: Complications and Adverse Eventsmentioning
confidence: 99%
See 4 more Smart Citations
“…As for the condition of donor eyes, which was mentioned in 4 studies, 25,28,30,32 no complications were reported. Following CLET, in 7 studies 25,28,31,34,37,38,41 it was reported that 18 eyes were suffering from microbial keratitis, but through fortified topical antibiotics or emergency keratoplasty 11 eyes were fully cured.…”
Section: Complications and Adverse Eventsmentioning
confidence: 99%
“…Eighteen articles [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] reported a success rate (Table 4) with 381 successful procedures in a total of 572 eyes. The pooled success rate was 67% (95% CI, 0.59-0.75; I 2 = 60%, P = 0.0006; Fig.…”
Section: Improvement In Ocular Surfacementioning
confidence: 99%
See 3 more Smart Citations